Genetic organization and mRNA expression of enolase genes of Candida albicans. - Postlethwait, P (1995)
In previous work, we cloned a Candida albicans cDNA for the glycolytic enzyme enolase and found a single, abundant enolase transcript on Northern (RNA) blots and a single protein on immunoblots, using antiserum raised against a recombinant enolase fusion protein. Because C. albicans enolase is abundantly produced during infection and elicits strong host immune responses, the mechanisms regulating enolase production are important for understanding the growth of C. albicans in vivo. To obtain more information on enolase gene expression by C. albicans, we used the enolase cDNA clone to investigate the genetic organization of enolase genes and the steady-state levels of enolase mRNA under several growth conditions. Gene disruption techniques in combination with Southern blot analyses of genomic DNA showed the presence of two enolase gene loci that could be distinguished by the locations of ClaI and Mn/I sites in their 3' flanking regions. Enolase steady-state mRNA levels were greatest during the middle phase of the logarithmic growth curve and were low during stationary phase. Minimal differences in enolase mRNA levels between yeast cells and hyphae were found. Propagation of C. albicans in glucose did not cause increased enolase mRNA levels compared with growth in a nonfermentable carbon source (pyruvate). It was concluded that two gene loci exist for C. albicans enolase and that enolase mRNA is constitutively produced at high levels during active metabolism.